2014
DOI: 10.5489/cuaj.1902
|View full text |Cite
|
Sign up to set email alerts
|

Plasmakinetic vaporization versus plasmakinetic resection to treat benign prostatic hyperplasia: A prospective randomized trial with 1 year follow-up

Abstract: Introduction: We evaluate the efficacy and outcomes of plasmakinetic vaporization (PKVP) and plasmakinetic resection (PKR) to treat benign prostatic hyperplasia (BPH).Methods: A total of 183 patients with BPH underwent plasmakinetic prostatic surgery between 2008 and 2012 at Kars State Hospital and Kafkas University Faculty of Medicine, Turkey. After clinical and preoperative evaluation, the patients were randomized to PKRP or PKVP groups sequentially by using computer-generated numbers. Group 1 included 96 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Physiologic saline irrigation is used instead of hyponatremic glycine or mannitol for the purpose of decreasing the risk of TUR syndrome and allowing for longer resection time to reach ''anatomic resection'' of the prostate. [7][8][9] Several previous randomized controlled trials (RCTs) of PKRP and TURP [10][11][12][13][14][15][16] have reported that PKRP has advantages of less bleeding, lower TUR syndrome incidence, shorter catheterization time and hospital stay. These studies, however, were limited by a short-term follow-up or a small sample size.…”
mentioning
confidence: 99%
“…Physiologic saline irrigation is used instead of hyponatremic glycine or mannitol for the purpose of decreasing the risk of TUR syndrome and allowing for longer resection time to reach ''anatomic resection'' of the prostate. [7][8][9] Several previous randomized controlled trials (RCTs) of PKRP and TURP [10][11][12][13][14][15][16] have reported that PKRP has advantages of less bleeding, lower TUR syndrome incidence, shorter catheterization time and hospital stay. These studies, however, were limited by a short-term follow-up or a small sample size.…”
mentioning
confidence: 99%